Accounting for Population Structure and Phenotypes From Relatives in Association Mapping for Farm Animals: A Simulation Study - Mancin, Enrico; Lourenco, Daniela; Bermann, Matias; Mantovani, Roberto; Misztal, Ignacy (Frontiers in Genetics, 2021)
Population structure or genetic relatedness should be considered in genome association studies to avoid spurious association. The most used methods for genome-wide association studies (GWAS) account for population structure but are limited to genotyped individuals with phenotypes. Single-step GWAS (ssGWAS) can use phenotypes from non-genotyped relatives; however, its ability to account for population structure has not been explored. Here we investigate the equivalence among ssGWAS, efficient mixed-model association expedited (EMMAX), and genomic best linear unbiased prediction GWAS (GBLUP-GWAS), and how they differ from the single-SNP analysis without correction for population structure (SSA-NoCor). We used simulated, structured fish, beef cattle, and dairy cattle populations with 1040, 5525, and 1400 genotyped individuals, respectively. The genomes were composed by 29 chromosomes, each harboring one QTN, and the number of simulated SNPs was 35,000 for the fish and 65,000 for the beef and dairy cattle populations. Males and females were genotyped in the fish and beef cattle populations, whereas only males had genotypes in the dairy population. Phenotypes for a trait with heritability varying from 0.25 to 0.35 were available in both sexes for the fish population, but only for females in the beef and dairy cattle populations. In the latter, phenotypes of daughters were projected into genotyped sires (i.e., deregressed proofs) before applying EMMAX and SSA-NoCor. Although SSA-NoCor had the largest number of true positive SNPs among the four methods, the number of false-negatives was two- to four-fold that of true-positives. GBLUP-GWAS was the method with the least number of true positives, followed by EMMAX and ssGWAS. Overall, the superiority of ssGWAS over EMMAX in detecting true-positives was 25%. This superiority was more evident when a fraction of phenotyped animals had genotypes or when genotyped animals had only progeny phenotypes. Single-step GWAS accounts for population structure and phenotypes from non-genotyped relatives, which makes this a more powerful method for association analysis.